Increasing the Stock Taking Process Accuracy for ISO 9001 Quality Management System Fulfilment at 2W EV Manufacturer, Cikarang, West Java - Maukar, Anastasia; Marcela, Anisa; Ratum, Athina Sakina (TALENTA Publisher, 2025)
The two-wheeled EV (2W EV) manufacturer at the centre of this study prioritizes efficiency, innovation, and adherence to ISO 9001:2015 quality requirements. However, the company encountered issues with its Supply Chain Management procedures during the ISO Surveillance 1 period, where one of the implementations was an internal audit in line with BPMS. Specifically, the results showed that the physical stock that matched the system was only 80%, which was very far from the KPI target of 95%. It hindered operations and impacted customer satisfaction. Business Process Improvement (BPI) was applied to examine the current stocking system. Comparing current processes with the best practices specified in BPMS and ISO 9001:2015 criteria was the first step in performing a thorough gap analysis. The results showed that human mistakes, machine calibration problems, a lack of standard operating procedures, inconsistent counting techniques, mixed scrap materials, and an unmanaged warehouse environment were causes of stock variations. The company made strategic changes, such as standardizing material labelling to avoid recording errors, substituting material loan for the interdepartmental purchasing system to increase accountability, and updating and enlarging SOPs to guarantee process uniformity. The business also installed an ERP system to enhance stock accuracy, facilitate real-time monitoring, and combine warehouse operations with digital tracking. As a result, by September 2024, the efficiency of stock control had increased by almost 86%. The increased stock control not only improves compliance with ISO 9001 standards, but it also increases overall operational efficiency by reducing production problems and increasing customer satisfaction.